Contribution to flow characterization through porous media - Miguel, A. F. (2013)
This paper reports a theoretical and experimental research in the field of mass transport through porous media. Thermodynamics was employed to model the change of mass inside porous media and the fluid flow through porous media. An experimental study was carried out to provide a thermodynamic chart of a porous medium and to infer the parameters required by the theoretical approach. The e ffect of the moisture content and temperature on fluid transport properties was also investigated.